TRANSOLECRANON FRACTURE-DISLOCATION: CONCEPTS AND FUNCTIONAL RESULTS OF SURGICAL TREATMENT - José da Mota Neto; Sebastião Alves da Cruz Neto; Leandro Furtado De Simoni; Diego Salzer Reis Zimmermmann; Fernando Brandão Andrade-Silva; Adriano Fernando Mendes Júnior (Acta Ortopédica Brasileira, 2023)
ABSTRACT Objectives: This study aimed to evaluate the functional results of the treatment protocol for the treatment of transolecranon fracture-dislocation, by surgical reduction and osteosynthesis with plate and screws, in patients attended at a referral hospital for orthopedic trauma, with a minimum follow-up period of six months. Methods: Twenty-five individuals treated surgically from January 2014 to November 2018 were selected for a primary observational longitudinal study using questionnaires to assess upper limb and elbow function (DASH and MEPS), quality of life (SF-12), pain (visual analog scale - VAS), and radiographic evaluation in anteroposterior and lateral views of the elbow. Results: Fifteen patients were male, and the mean age was 46.8 years. All participants had their fractures consolidated, with no radiolgraphic signs of implant failure, or degenerative arthritis. Mean range of motion was reduced relative to the contralateral limb: 102.6º for flexion-extension and 132.8º for pronation-supination. The mean MEPS and DASH scores were 89.6 and 16.5 respectively. There was no residual pain in 84% of the cases according to the VAS. Conclusion: The surgical treatment proposed for transolecranon fracture-dislocations showed satisfactory results according to MEPS, DASH scores and quality of life measures. Evidence Level IV; Retrospective observational study.